Determination of Contrast Timing by Time-Resolved Magnetic Resonance Angiography in Patients With Bidirectional Glenn and Hemi-Fontan Anastomoses. Issue 5 (30th September 2022) - Yekeler, Ensar; Ramirez-Suarez, Karen I.; Rapp, Jordan B.; White, Ammie M.; Otero, Hansel J.; Whitehead, Kevin K.; Harris, Matthew A.; Fogel, Mark A.; Biko, David M.
Abstract : Purpose: Children with single-ventricle congenital heart disease undergo a series of operations to maintain their pulmonary circulation including bidirectional Glenn (BDG) or hemi-Fontan in the second stage to create a superior cavopulmonary anastomosis. We aimed to optimize cardiovascular angiography protocols by determining optimal contrast timing of pulmonary and systemic circulation on magnetic resonance angiography (MRA) performed with the technique of time-resolved imaging with interleaved stochastic trajectories (TWIST). Methods and Materials: Cardiac TWIST MRA with lower extremity (LE) contrast injection was analyzed in 92 consecutive patients with a BDG or hemi-Fontan anastomosis. Contrast arrival time to inferior vena cava was set to zero to determine the relative time-to-peak (TTP) of the target vessels. Time-to-peak of each vessel was compared by age (<2 or ≥2 y), ejection fraction (<54% or ≥54%), the median values of heart rate (<111 or ≥111 beats per minute), body surface area (BSA, <0.59 or ≥0.59), cardiac index (<6.04 or ≥6.04), and indexed ascending aorta flow (AscAo_i, <5.3 or ≥5.3). The TTP of the vessels was also correlated with the volumetric parameters. Results: The mean age of 92 patients (32 female, 60 male) was 3.1 years (0.7–5.6 years). With LE injection, the first peak was depicted in AscAo. Time-to-peak of the pulmonary arteries was approximately 9 seconds later than AscAo. The TTP difference between pulmonary arteries and AscAo was shorter in high heart rate group (8.3 vs 10 seconds, P < 0.001). The TTP difference between AscAo and the mean of pulmonary arteries was significantly shorter in high cardiac index group (8.4 vs 9.9 seconds, P < 0.01) and high AscAo_i group (8.7 vs 9.7 seconds, P = 0.03). The TTP differences were not significant by age, ejection fraction, and BSA. Cardiac index and AscAo_i were negatively correlated with all TTPs except AscAo. The ejection fraction, stroke volume, and atrioventricular regurgitation fraction did not correlate with the TTP. Conclusions: In patients with BDG or hemi-Fontan anastomosis, TTP of the pulmonary arteries on TWIST MRA via LE intravenous injection is approximately 9 seconds later than AscAo, approximately 8 and 10 seconds later in high and low heart rate groups, respectively. Cardiac index and AscAo_i have less effect on the TTP than the heart rate. There was no TTP difference of the pulmonary arteries by age, BSA, and ejection fraction and no correlation with ejection fraction, stroke volume, and atrioventricular regurgitation fraction. These data can be used to guide timing of pulmonary arterial enhancement of single-ventricle patients after BDG or hemi-Fontan anastomosis.